STUDI ANALISIS PENERAPAN PEMBELAJARAN MELALUI PENDEKATAN STUDENT ACTIVE LEARNING DI SMP NEGERI 2 DAMPAL SELATAN - Samsul B. Liasi (Scolae: Journal of Pedagogy, 2019)
Active learning aims to strengthen and facilitate the stimulus and response of students in learning, so the learning process becomes fun, not boring for them. By providing active learning strategies for students can help their memory, so they can be delivered to the learning objectives successfully. This is not considered in conventional learning.The purpose of this study is to determine the application of learning through the active student learning approach in SMP Negeri 2 South Dampal and to find out the obstacles and solutions encountered in the application of learning through the student active learning approach.The research method used is a qualitative approach by describing and interpreting the meaning of data. Furthermore, to obtain data in accordance with the problem, data collection is done by observation, interviews, questionnaires, and documentationThe results showed that the application of active learning can be achieved well, by observing students' attitudes and changes both in cognitive, affective, and psychomotor values.